Les mécanismes de construction de mots en godié, langue kru de Côte D'Ivoire - N'dré, Damanan (Linguistik Online, 2016)
This article analyzes the mechanisms of word building in Godié, a Kru language spoken in Côte d’Ivoire. Two processes underly these mechanisms: morphological and syntactic methods. Morphological processes refer to constructed words and syntactic processes refer to lexicalized syntactic sequences. At the morphological level, are generated by the constructed word by suffix and words constructed by juxtaposing two or three tokens. The language has three verbal derivative suffixes. These are -lɩ, -nö and -mà. There is no process in the language whereby a verb is derived from a noun. For words constructed by juxtaposition of tokens, there are generally three types obtained by. In other words, two or three nouns can combine to create new words; as a noun and an adjective can combine to create new words. As for new words, created by combining two or three names, it has been shown that the Internal underlying structure of bipartite type derived from a tripartite structure surface. However, the existence of the tripartite structure is allowed; but it emerges, within the language, from idiosyncratic phenomena. Even in lexicalized syntactic sequences, it was also observed that internal bipartite structure underneath. Moreover, between words constructed by combining three formants and lexicalized syntactic sequences, the limit is blurred. In the language, words constructed as syntactic lexicalized sequence may be a dictionary entry. Our study shows that the concept of a morphological right head is untenable. In the language, in fact, words may be constructed with both left and with right morphological heads. In addition, some words are constructed with morphological head whatsoever, as in many languages around the world.